AN ENRICHMENT IMPLEMENTATION IN THE EDUCATION OF GIFTED STUDENTS: BIOMIMICRY WITH THE MACRO, MICRO, AND SUB-MICRO NATURE OF FRESHWATER CREATURES - Mirici, Semra; Tanalp, Tugce Deniz; Tuysuz, Mustafa; Tuzun, Ummiye Nur (International Online Journal of Education and Teaching, 2021)
Biomimicric implementations provide positive contributions to the development of many abilities such as problem solving, creative thinking and productivity by enabling students to look at nature from a different perspective. For this reason, in this study, it was investigated how the biomimicric applications of the macro, micro, and sub-micro nature of freshwater creatures were reflected in their arguments with special gifted students. The research was planned as a summer workshop in an institution that teaches with special gifted students in Ankara in the 2017-2018 academic year, and was carried out on the basis of case study from qualitative research patterns with eight gifted students. In a two-stage study, gifted students conducted microscopic and literature research on freshwater creatures in the first stage and made drawings about the macro, micro, and sub-micro nature of living things. In the second phase, they discussed their biomimicric prototypes in groups and explained them with their arguments. In the study based on document analysis, the data were obtained from students' worksheets and analyzed by content analysis. As a result of the research, it can be said that the concept images of gifted students develop with macro, micro, and sub-micro drawings and the quality of the arguments they construct has become more qualified during the process, and the application contributes to their creative and analytical thinking.